THE PESANTREN-BASED RULING ELITE IN SUMENEP IN THE POST-NEW ORDER INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2009)
This paper discusses a dominant group in local politics of Sumenep that is based on a pesantren network that is usually referred to as the Bani Syarqawi. The author argues that the superiority of religious clerics (kyai) over the mass in Sumenep has been mainly based on their adaptability to the transformational change of their role from traditional-charismatic to rational-authoritative by means of educational excellence and genealogical network that is both powerful and full of conflict. The social significance of the superiority found its way through a social change that enabled the religious elite to be the dominant elite group in Sumenep when the power of their royal counterpart declined rapidly. Equipped with Weberian model of authority, the author argues that the formalistic tendency of elite theory can be balanced with a perspective that elite can develop and exercise power over the mass even they are outside the formal structure of politics.